RINTISAN KEWIRAUSAHAAN MELALUI BISNIS TEH REMPAH BAGI PENGGERAK PEREKONOMIAN KELUARGA DI KELURAHAN GUNUNG SUGIH - Khodijah, Ina; Munawaroh, Munawaroh; Haeriyah, Haeriyah; Perdiansyah, Nanda Kurnia; Fitriyah, Fitriyah; Ariyandhi, Muhamad Andy; Hardiansyah, Sandi; Nurazizah, Windi (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The existence of Bina Bangsa University through KKM – PKM activities needs to be felt for its benefits, especially for the people of Gunung Sugih Village, Cilegon City. This is a concern for the service team because there are still many elements of the community that need to contribute to improving community welfare, one of which is PKK women in Gunung Sugih Village, Ciwandan District, Cilegon City. The purpose of this service program is to increase insight and skills as an entrepreneurial provision for PKK women in Gunung Sugih Village through the manufacture of spice tea made from turmeric, ginger, lemongrass and galangal. The methods used in this service are 1) the preparation stage (input), 2) the implementation stage (production process) and 3) monitoring, observation, evaluation and reporting of the results. The result of this service is input, conducting a survey to find out the environmental conditions around Gunung Sugih village. Then conduct socialization to PKK women in the Gunung Sugih environment. Next is a feasibility study on the business that will be run by providing a seminar on new business start-ups through the spice tea business. The last stage is the selection of materials and the provision of places as well as facilities and infrastructure to support the production process. The process (production), the process of making spice tea starts from the preparation of ingredients and tools until the product is ready to be marketed. Output, which is the result of spice tea drinks that are ready to be consumed and marketed to consumers. The last is evaluation, which is that this stage is carried out when the production of spice tea products has been completed. At this stage, we will review the shortcomings that make consumers uncomfortable with our products. The conclusion of the KKM - PKM program can provide skills to PKK women to remain innovative and creative in processing the business of herbal tea spices that have become a characteristic of Indonesia, provide opportunities for PKK women to practice entrepreneurship with a comprehensive understanding of the concept of entrepreneurship, and build the spirit of PKK women to continue doing business